Arsenic in Drinking Water and Lung Cancer Mortality in the United States: An Analysis Based on US Counties and 30 Years of Observation (1950–1979). (13th June 2016) - Ferdosi, Hamid; Dissen, Elisabeth K.; Afari-Dwamena, Nana Ama; Li, Ji; Chen, Rusan; Feinleib, Manning; Lamm, Steven H.
Abstract : Background. To examine whether the US EPA (2010) lung cancer risk estimate derived from the high arsenic exposures (10–934 µ g/L) in southwest Taiwan accurately predicts the US experience from low arsenic exposures (3–59 µ g/L). Methods . Analyses have been limited to US counties solely dependent on underground sources for their drinking water supply with median arsenic levels of ≥3 µ g/L. Results . Cancer risks (slopes) were found to be indistinguishable from zero for males and females. The addition of arsenic level did not significantly increase the explanatory power of the models. Stratified, or categorical, analysis yielded relative risks that hover about 1.00. The unit risk estimates were nonpositive and not significantly different from zero, and the maximum (95% UCL) unit risk estimates for lung cancer were lower than those in US EPA (2010). Conclusions . These data do not demonstrate an increased risk of lung cancer associated with median drinking water arsenic levels in the range of 3–59 µ g/L. The upper-bound estimates of the risks are lower than the risks predicted from the SW Taiwan data and do not support those predictions. These results are consistent with a recent metaregression that indicated no increased lung cancer risk for arsenic exposures below 100–150 µ g/L.